2010
DOI: 10.1111/j.1524-4725.2010.01563.x
|View full text |Cite
|
Sign up to set email alerts
|

Elastometry and Clinical Results After Bipolar Radiofrequency Treatment of Skin

Abstract: Elastometry data showed an average decrease in Young's Modulus and retraction time, both of which suggest that radiofrequency bipolar treatment resulted in more youthful skin. Better mechanical characteristics were consistent with improvements in wrinkles, laxity, and skin quality and appearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 16 publications
1
38
0
Order By: Relevance
“…These data are consistent with the literature, 13 and are in favor of the bipolar technology, as the elastic fibers seem to significantly decrease after monopolar treatment. 2 The epidermis did not display any significant damage apart from a transient erythema at the end of the in vivo treatments.…”
Section: Discussionsupporting
confidence: 92%
“…These data are consistent with the literature, 13 and are in favor of the bipolar technology, as the elastic fibers seem to significantly decrease after monopolar treatment. 2 The epidermis did not display any significant damage apart from a transient erythema at the end of the in vivo treatments.…”
Section: Discussionsupporting
confidence: 92%
“…The elastosis score was also statistically significantly lower after the treatments, which is in agreement with elastometry findings after using another fractional RF system equipped with 5-microneedle-electrode pairs. 40 A previous study demonstrated that 90% of subjects with skin type II to IV showed improvement in smoothness and wrinkling, 87% in skin tightness, and 83% in skin brightness 1 month after three sublative RF treatments. 38 On the other hand, Wanner and colleagues showed that 73% of patients had 51% to 75% improvement in facial photodamage 9 months after a series of nonablative FP resurfacing.…”
Section: Discussionmentioning
confidence: 98%
“…Elastic fiber regeneration has been reported following radiofrequency treatments 21 with evidence of a juvenile reticular pattern. 22 Therefore, our results are likely to be related to the radiofrequency sequential applications.…”
Section: Discussionmentioning
confidence: 99%